Energy Efficient Data Transmission for Sensors with Wireless Charging - Xiaolin Fang (Sensors, 2018)
This paper studies the problem of maximizing the energy utilization for data transmission in sensors with periodical wireless charging process while taking into account the thermal effect. Two classes of problems are analyzed: one is the case that wireless charging can process for only a limited period of time, and the other is the case that wireless charging can process for a long enough time. Algorithms are proposed to solve the problems and analysis of these algorithms are also provided. For the first problem, three subproblems are studied, and, for the general problem, we give an algorithm that can derive a performance bound of ( 1 − 1 2 m ) ( O P T − E ) compared to an optimal solution. In addition, for the second problem, we provide an algorithm with 2 m 2 m − 1 O P T + 1 performance bound for the general problem. Simulations confirm the analysis of the algorithms.